Experimental Study of the Dynamic Compressive and Tensile Anisotropic Mechanical Properties and Failure Modes of Shale - Qian Dong; Hao Tong; Jinshan Sun; Songlin Peng; Jijie Jia (Sensors)
To investigate the dynamic compressive and tensile mechanical properties and failure modes of shale, split Hopkinson pressure bar (SHPB) and high-speed imaging and digital image correlation (DIC) technologies were adopted. Dynamic impact compression and Brazilian splitting tests of shale samples at five different bedding angles of 0°, 30°, 45°, 60°, and 90° (angles between the dynamic compressive loading direction or the actual dynamic tensile loading direction and the normal direction of the bedding planes) were conducted to reveal the influence of the bedding angle, strain rate, and impact velocity on the dynamic compressive and tensile mechanical properties and failure modes of shale. The experimental results indicate that the dynamic compressive and tensile strengths, as well as the failure modes, of shale exhibit significant anisotropy. The dynamic strength of the shale increased with the strain rate and impact velocity, while it decreased initially and then increased with the increase in the bedding angle. The failure modes of shale under dynamic compressive and tensile loads are closely related to the bedding angle, strain rate, and impact velocity.